Karakteristik Usaha Ternak Sapi Terintegrasi Dengan Tanaman Padi Di Distrik Semangga Kabupaten Merauke - Nurliah Nurliah; Adrianus Adrianus; Ineke Nursih Widyantari; Abdul Rizal (Musamus Journal of Livestock Science, 2022)
This research is a qualitative research which describes the condition of farmers and ranchers in the research location based on the observed variables. The method used is a survey method, with the sampling technique is Stratified Random Sampling. This location was chosen because it is one of the districts where the majority of the people are farmers and breeders with an integrated system of rice plants and cattle, while the population in this study is the people of the Semangga District who carry out integrated farming of rice and cattle raising. Sources of data in this study are primary data and secondary data. Data collection was carried out using several techniques, namely (a) Observation, namely direct observation in the field (b) Interview, conducted directly to farmers and ranchers with the help of questionnaires and (c) Documentation, namely taking pictures in the field. The data analysis used is descriptive analysis by looking at the average and percentage on each business characteristic. The conclusion of this study is that the average number of cattle kept is 2 heads with a land area of 3 ha, the highest percentage of education level is SD (49%) and the lowest is SI (1%), the average age of the respondents is in the productive age, namely 26-50 years (94%), the highest length of business is 6-10 years (53%) and the average family responsibilities are 1-4 people (94%).